THE CHALLENGES WOMAN POLITICIANS IN INDONESIA (REPRESENTATION MEGAWATI SOEKARNOPUTRI AND PUAN MAHARANI IN MEDIA) - Netty Dyah Kurniasari (JOURNAL OF LAW AND GOVERNMENT SCIENCE, 2015)
According Braden , journalists ' frequently asked questions women politicians that they do not ask male politicians " and describes them ( women politicians ) " the manner and words that emphasize the traditional role of women and more focused on the appearance and behavior " .Women candidates and women leaders described and denigrated by the media by using " gender -specific terms " .Research about the image of women politicians in the media has a lot to do but the majority of the research taking foreign context . The focus of this research is about the portrayal of women politicians in the media . More specifically the depiction of the Chairperson Strunggle-Indonesia Democratic  Party (PDI-P) Megawati and Puan Maharani.Both  of them a leader and party officials in Indonesia .Kompas Online ( website Kompas.Com ) defined as research subjects because it is known that the media gives attention to gender issues and gender equalitySubject this research is  Kompas as national newspapaer in Indonesia. Research method to be used is a qualitative textual analysis. Through this method made the search for implicit and ideological meaning behind the text and written transcripts.The results shows that Woman are Forbidden (‘Haram’) Being Leader, Women`s Ability is  Doubtful ; Women More Prone to  Campaign Feminine Issue; Women politicians Under the Shadow Men; Female Age Being  Problem; Women As Unifying , Adhesives and Harmony Keeper and Women is  EmotionalKeywords:  woman politicians, media, construction of reality, representation